The Effect of Work Stress and Organizational Culture on Work Performance with Organizational Commitment as an Intervening Variable at the Bank Indonesia Representative Office in North Sumatra Province - Dadang Fahruzi Ritonga; Isa Indrawan (International Journal of Management, Economic and Accounting, 2024)
Employees are not mere resources, but more in the form of capital or assets for institutions or organizations. Therefore, a new term emerged outside of human resources, namely human capital. Here, human resources are seen not only as the main asset, but as an asset that has value and can be multiplied, developed (compared to an investment portfolio) and not the other way around as a liability (burden). Here, the perspective of human resources as an investment for institutions or organizations is more prominent. The results of this study are as follows: Organizational Culture has a positive and significant effect on Organizational Commitment with a value of 0.518 and a significant 0.000 Organizational Culture has a positive and significant effect on Work Performance with a value of 0.195 and a significant 0.035. The Organization's commitment has a positive and significant effect on Work Performance with a value of 0.554 and a significant 0.000. Work Stress had a negative and significant effect on Organizational Commitment with a value of -0.412 and a significant 0.000. Work Stress had a negative and significant effect on Job Achievement with a value of -0.211 and a significant 0.036. Organizational Culture has a positive and significant effect on Work Achievement through Organizational Commitment with a value of 0.287 and a significant 0.000. Work Stress has a negative and significant effect on Work Achievement through Organizational Commitment with a value of -0.228 and a significant value of 0.001.